DISEMINASI MODERASI BERAGAMA DALAM ROHANI ISLAM (ROHIS) MAN 2 PANDEGLANG - Royhatudin, Aat; Maryam, Siti; Rosita, Desyi; Kurnaesih, Uun (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
The potential for radicalism and exclusivity towards students is more about understanding texts without being described in context, so it is important to teach religious moderation, especially at the high school level. This study aims to analyze and examine the process of disseminating religious moderation in character building as religious education for students is very important to do, namely to strengthen their character so that the negative behavior of others does not easily affect them. In practice, religious moderation requires management to run optimally. This study uses a descriptive qualitative approach with the type of case study. The results showed that religious moderation which was disseminated in Rohis religious activities was strengthened by madrasa management through the implementation of activities by utilizing social media, that religious moderation in madrasas and boarding schools carried out the importance of religious moderation in instilling various values of moderation in students, instilling and applying values. the value of goodness exemplified by the Prophet Muhammad SAW.